Care trajectories of users with severe psychological distress in the Psychosocial Care Network: Existentialist perspectives - Polli, Carolina Beckert; Schneider, Daniela Ribeiro (Seven Editora, 2023)
This study aims to present partial results of broader research that resulted in the master’s thesis entitled “Life Stories and Severe Psychic Suffering from the Perspective of Existentialist Psychology: Existential Narratives.” The study aimed to investigate the processes of constitution of severe psychic suffering from the autobiographical narratives of users of the Psychosocial Care Network (RAPS) in a municipality in the north of Santa Catarina, Brazil. The narratives were elucidated based on the perspective of Existentialist Psychology, outlined by the French philosopher Jean-Paul Sartre (1905-1980) in his intellectual trajectory, in which his ontology and method replace the subject in his dialectical and temporal constitution. The elicitation of the narratives followed a script adapted from the “Life Story Interview” developed by the American researcher McAdams (2012). The division and conduction of the narratives proposed by the script served as a basis analyzing and gatheringng the singular elements present in the axes of meaning. This text aims to discuss the notion of care from an existentialist perspective based on the narratives of these subjects, specifically, at the time of the interview in which they were invited to tell their care trajectories, which refers to the movement they made in the search for help for their suffering condition. The discussion on the notion of care from Sartre sought to bring this theory closer to the logic of an expanded clinic as the foundation of care in Psychosocial Care. Finally, it is considered that the logic of the expanded clinic, associated with an existentialist understanding of human suffering, can enable the construction of emancipatory practices in the territory, effectively breaking with the biomedical logic of a purely curative nature. DOI:https://doi.org/10.56238/globalhealthprespesc-056